Research on the durability of nano-SiO2 and sodium silicate co-modified recycled coarse aggregate (RCA) concrete. (16th May 2023) - Liu, Xiaoyan; Xie, Xian; Liu, Ruidan; Lyu, Kai; Zuo, Junqing; Li, Shijie; Liu, Li; Shah, Surendra P.
Highlights: The substitution ratio relationship between RCA and MRCA on mechanical properties was established. The influence of NMS on RAC on durability was investigated. The optimization of NMS on the pore structure of RAC was investigated. The mechanism of NS and sodium silicate cooperative modification of RCA and ITZ was investigated. Abstract: Compared with natural aggregate (NA), recycled coarse aggregate (RCA) is of lower strength and higher porosity due to the attached mortar, which limits the application of RCA. In this paper, the nano SiO2 -sodium silicate mixed solution (NMS) was prepared and used to modify RCA by improving the properties of the attached mortar. Three groups of concrete with NA, RCA, and modified RCA (MRCA), respectively, were prepared. The modification effects of NMS on the concrete were illustrated in regards to the mechanical properties and durability (impermeability, chloride ion resistance, and freezing-thawing resistance). Results indicated that the concrete with the MRCA had higher mechanical properties, better durability properties, and lower air void content. Then, the surface morphology of the MRCA and interfacial transition zone (ITZ) in concrete were both examined by scanning electron microscope (SEM) to understand the modification effect of NMS. It showed that the NMS can fill the pores and repair the cracks on the attached mortar by filling effect (brought by nano SiO2 ) and film-forming effect (brought by sodium silicate). Moreover, nano SiO2 and sodium silicate could also participate in secondary hydration reaction to form C-S-H gel and strengthen the microstructure of ITZ. The coupling effect both result in the improved mechanical and durable properties of the concrete prepared with MRCA.